Transfer Teknologi Yogurt Nabati Berbasis Kacang Hijau (Vigna radiata) - Winarsi, Hery; Ramadhan, Gumintang Ratna; Khoiriani, Izzati Nur (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2021)
This activity aims to transfer the technology for making vegetable yogurt based on mung bean to the producers of Yogurt Sehati, North Purwanegara Village, Purwokerto Utara and the surrounding community, as well as motivating participants to use it. The method used is counseling, practice, and explanation of product benefits for health. This activity begins with the selection of strategic target audiences, capable and able to carry out all activities. A total of 16 ladies and gentlemen, who work as cow's milk yogurt producers, housewives, bread producers, and chicken cream producers in the local village, acted as participants. In this activity, pre-test and post-test were carried out, followed by counseling on mung bean yogurt products and their benefits, and manufacturing practices, as well as business feasibility calculations. The results of this activity showed that the participants were very enthusiastic, as seen from the increase in test scores from 70.67 to 80.1 (P=0.04). When the practice of making mung bean yogurt was carried out, there were several questions asked from the participants, complete with the requirements for producing it. In conclusion, participants were interested in developing plant-based yogurt products that were felt to be easy to make, inexpensive to invest in, but great in benefits.